Biological efficiency of chilli + amaranth intercropping system under fertigation - Innazent, Anitrosa; Anitha, S.; Thomas, C. George; Prameela, K.P.; Beena, V. I. (Journal of Tropical Agriculture, 2019)
An experiment was conducted at Water Management Research Unit, Vellanikara during January to July 2017 to study the biological efficiency of chilli+ amaranth intercropping system under different nutrient and water regimes. The treatments consisted of chilli + amaranth intercropping system planted at two different planting geometries viz., normal row planting and paired row planting, three nutrient levels viz., 100, 75 and 50 per cent NPK recommendation of both crops as fertigation and two irrigation levels viz., 100 per cent Epan and 75 per cent Epan along with two controls viz., chilli pure crop and amaranth pure crop. Biological efficiency of intercropping system was assessed by calculating LER, LEC, ATER, RCC and CEY. Chilli + amaranth intercropping under normal row planting produced significantly higher LER (2.84) compared to paired row planting. The intercropping system fertilized at 100 per cent of the recommended NPK dose to both crops showed the highest LER (2.81) compared to lower doses. Irrigation at 100 per cent Epan recorded significantly higher values of LEC (1.54) and ATER (2.56). Chilli equivalent yield was higher in chilli+ amaranth intercropping system (16553 kg/ha) compared to pure crop. The higher values of LER (>1.0), LEC (> 0.25), ATER and CEY revealed the biological efficiency of chilli + amaranth intercropping system compared to pure crop system.